2011
DOI: 10.1089/scd.2010.0336
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Murine Embryonic Stem Cells' Self-Renewal and Pluripotency with Increase in Proliferation Rate by a Bovine Granulosa Cell Line-Conditioned Medium

Abstract: Murine embryonic stem cells (mESCs) are pluripotent cells that can be propagated in an undifferentiated state in continuous culture on a feeder layer or without feeders in the presence of leukemia inhibitory factor (LIF). Although there has been a great advance since their establishment, ESC culture is still complex and expensive. Therefore, finding culture conditions that maintain the self-renewal of ESCs, preventing their differentiation and promoting their proliferation, is still an area of great interest. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 39 publications
0
23
1
Order By: Relevance
“…R1 and Ainv15 ESC lines are commercial lines purchased from ATCC. They were cultured and differentiated as previously described [ 13 15 ]. The iPSC-20 line was derived and validated previously by us [ 16 ], and cultured and differentiated as previously described [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…R1 and Ainv15 ESC lines are commercial lines purchased from ATCC. They were cultured and differentiated as previously described [ 13 15 ]. The iPSC-20 line was derived and validated previously by us [ 16 ], and cultured and differentiated as previously described [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…The E14-derived Ainv15 and R1 mESC lines were obtained from ATCC and cultured as previously described [ 11 , 12 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…We have recently shown that conditioned medium (CM) from a bovine granulosa cell line (BGC-CM) is able to maintain mouse pluripotent stem cells’ self-renewal, including ESC and induced pluripotent stem cells (iPSC), while preserving their unique properties, in culture without Leukemia Inhibitor Factor (LIF) addition [ 11 , 12 ]. Pluripotent stem cells growing on BGC-CM expressed stem cell markers and remained pluripotent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different types of stem cell‐derived CM have shown various effects on ESCs or iPSCs, such as maintenance of the self‐renewal of ESCs and iPSCs without LIF addition and efficient differentiation of ESCs or iPSCs . Recently, CM has shown therapeutic efficacy in acute lung injury, stroke, and Huntington's disease .…”
Section: Discussionmentioning
confidence: 99%